PENGARUH RISIKO PERBANKAN TERHADAP KINERJA BANK (Studi pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2022) - Tugiyo Putri, An'umillah Dhi'fan; Purwanto, Agus (Diponegoro Journal of Accounting, 2024)
This study aims to examine and analyze the effect of Credit Risk, Liquidity Risk, Market Risk, Operational Risk, and Capital Adequacy on Bank Performance. The sample consists of Commercial Banks listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2022. The purposive sampling technique was used, resulting in 40 banks as the research samples. Independent variables were measured using specific ratios, namely NPL for Credit Risk, LDR for Liquidity Risk, NIM for Market Risk, and BOPO for Operational Risk, as well as CAR for Capital Adequacy. The dependent variable, Bank Performance, was measured using the ROA ratio. The analysis results indicate that Credit Risk, Liquidity Risk, and Capital Adequacy do not have a significant effect on Bank Performance, while Market Risk has a significant positive effect on Bank Performance, and Operational Risk has a significant negative effect on Bank Performance.